2020
DOI: 10.3389/fgene.2019.01322
|View full text |Cite
|
Sign up to set email alerts
|

Combining Citizen Science and Genomics to Investigate Tick, Pathogen, and Commensal Microbiome at Single-Tick Resolution

Abstract: The prevalence of tickborne diseases worldwide is increasing virtually unchecked due to the lack of effective control strategies. The transmission dynamics of tickborne pathogens are influenced by the tick microbiome, tick co-infection with other pathogens, and environmental features. Understanding this complex system could lead to new strategies for pathogen control, but will require large-scale, high-resolution data. Here, we introduce Project Acari, a citizen science-based project to assay, at single-tick r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 83 publications
1
26
1
Order By: Relevance
“…In contrast to our results, three recent studies have shown no significant difference in bacterial diversity associated with Borrelia infection status [ 58 , 73 , 74 ], and a fourth study was ambiguous [ 28 ]. However, one of these studies reported results for a mix of females and males [ 73 ], which would have increased the variance in an already noisy system [ 17 ]. A second study [ 74 ] analyzed nymphs of Ixodes pacificu s and found no significant differences in richness or evenness.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our results, three recent studies have shown no significant difference in bacterial diversity associated with Borrelia infection status [ 58 , 73 , 74 ], and a fourth study was ambiguous [ 28 ]. However, one of these studies reported results for a mix of females and males [ 73 ], which would have increased the variance in an already noisy system [ 17 ]. A second study [ 74 ] analyzed nymphs of Ixodes pacificu s and found no significant differences in richness or evenness.…”
Section: Discussioncontrasting
confidence: 99%
“…This strongly influences the final result, as prior to computationally removing the Rickettsia symbiont in the former study, Kwan et al 107 also did not observe significant differences in either species richness or evenness. This latest observation was recently confirmed by Chauhan et al 122 which analysed the microbial communities of I scapularis collected via citizen scientific approaches in the USA. They did not find any association between the microbiome diversity of a tick and its probability of carrying B burgdorferi .…”
Section: Tick Microbiome Interactions With Tick‐borne Pathogensmentioning
confidence: 55%
“…Many microbiome studies have documented a pattern of increasing relative abundance of endosymbionts through development of Ixodes spp. from larva, to nymph, to adult stages [35,47,[55][56][57]. Rickettsia accumulation by adult female ticks is thought to be an adaptation to facilitate transovarial transmission of the endosymbiont to eggs, underlining the importance of endosymbionts to tick survival and development [46,51,58].…”
Section: Interstadial Changes In the Microbiomementioning
confidence: 99%
“…In multiple studies of I. scapularis that examined the relative abundance within sequenced 16S rRNA amplicons, adult female ticks were observed to exhibit a higher proportion of Rickettsia endosymbionts than males and to have lower microbiome diversity as measured by Shannon diversity or overall richness [35,47,55,56]. However, Tokarz et al performed detailed qPCR analysis of male and female ticks separately and did not observe significant differences in bacterial abundance between male and female I. scapularis [47].…”
Section: Interstadial Changes In the Microbiomementioning
confidence: 99%